Destins de femmes - Isbell, John (Open Book Publishers, 2023)
Destins de femmes is the first comprehensive overview of French women writers during the turbulent period of 1750-1850. John Isbell provides an essential collection that illuminates the impact women writers had on French literature and politics during a time marked by three revolutions, the influx of Romantic art, and rapid technological change.